2023
DOI: 10.1097/md.0000000000032563
|View full text |Cite
|
Sign up to set email alerts
|

Osteochondritis dissecans of the metacarpal head in a soldier treated with osteochondral autograft transplantation surgery: A case report

Abstract: Rationale: Osteochondral autograft transplantation surgery (OATS) was introduced as a treatment for hand osteochondritis dissecans (OCD), and successful results were reported. However, the cartilage height of the donor plug has not yet been established compared with that of other joints. We present a case using OATS for OCD of the 3rd metacarpal (MCP) head that occurred in a soldier and the findings of magnetic resonance imaging (MRI) images taken at 12 weeks after surgery.Patient concerns: A 21-year-old male … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Multiple grafts are able to resurface 80-100% of the damaged area [8], but studies have shown that having a gap between cartilages can result in poor histologic properties of the cartilage [9]. The current tool for removing the donor graft in OAT surgery is a manually inserted hollow cylindrical rod that is used to break the base of the donor graft [10,11], as shown in Figure 1. After removing the donor graft, its base is cut to implant into the defect site [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple grafts are able to resurface 80-100% of the damaged area [8], but studies have shown that having a gap between cartilages can result in poor histologic properties of the cartilage [9]. The current tool for removing the donor graft in OAT surgery is a manually inserted hollow cylindrical rod that is used to break the base of the donor graft [10,11], as shown in Figure 1. After removing the donor graft, its base is cut to implant into the defect site [12].…”
Section: Introductionmentioning
confidence: 99%
“…is used to break the base of the donor graft [10,11], as shown in Figure 1. After removing the donor graft, its base is cut to implant into the defect site [12].…”
Section: Introductionmentioning
confidence: 99%